Alterações fisiológicas em cacaueiro (Theobroma cacao L.) cv. Catongo cultivado sob condições de hipóxia na presença de silício - Marques, Helder Ivo Pandolfi (2015)
The cocoa is grown throughout the tropical region of the world and its almond is the main ingredient of chocolate. Some cultivation sites tend to suffer from flooding during a period of the year. The low availability of oxygen caused by flooding, induces changes in physiological and morphological processes, modifying the development and growth of plants. Aeration of the nutrient solution is necessary to provide oxygen to the roots of plants grown hydroponically. Silicon is beneficial for several crops, especially when subjected to some kind of stress, can help alleviate the damage caused by flooding. In the literature, there is no report of cocoa cultivation with omission and silicon level, mainly because the presence of this element in all soil types. Based on this prerogative, an experiment was conducted with cocoa seedlings cv. Catongo. The experiment was conducted in CEUNES greenhouse, located in the municipality of São Mateus-ES, in a completely randomized design with four repetitions being one plant on each repetition in the first and second evaluation time and the third used two plants per replicate. The treatments were arranged in a 2x3x5 factorial arrangement, being with and without aeration of the nutrient solution, the three sampling times and five silicon levels (0, 0.5, 1.0, 1.5, 2.0 mmol L-1 ). The evaluations were divided into two chapters, the first objective was to evaluate the growth variables, foliar silicon content and x photosynthetic pigments content. The second chapter, gathered the character fluorescence of chlorophyll a and gas exchange. Based on the results, were observed influence of lack of aeration leaves concentration of silicon, degradation of photosynthetic pigments, chlorophyll fluorescence and gas exchange. It can be seen the isolated effect of silicon on some physiological parameters of plants not subjected to stress, as well as in plants submitted in this case relieves stress caused by lack of aeration.